‘Social Mix’ as ‘Sustainability Fix’? Exploring Social Sustainability in the French Suburbs - Carpenter, Juliet (2018)
The French suburbs, or banlieues, have long been associated with marginalization and peripheralization, characterized by unemployment, a high proportion of ethnic minority populations and low education attainment levels. Since 2000, the ‘crisis’ of the banlieue has been addressed through a policy of ‘social mixing’ which aims to promote mixed communities in certain neighbourhoods, to dilute the ‘problematic elements’ of the suburbs. This ‘social sustainability fix’ however has had mixed results. Questions can be raised over whether a policy based on increasing a neighbourhood’s social mix is an appropriate sustainability fix for the suburbs, and whether it has actually resulted in the outcomes that were intended. Rather than encouraging social integration, it is argued here that the policy of social mixing reinforces segregation and has done little to tackle inequalities and social exclusion. We suggest that there are alternative solutions to the challenges of fostering social sustainability in the suburbs, which could be implemented in partnership with citizens and neighbourhoodbased groups (associations) that would be more effective in addressing social sustainability solutions in the future.